Febrile Seizures: The COVID-19 Pandemic and Beyond - Betül Diler Durgut; Emine Tekin; Cevriye Ceyda Kolaylı (Çocuk Dergisi)
Objective: Febrile seizures are common reasons for admission to paediatric emergency departments. There is evidence suggesting that the frequency, severity, and seasonal distribution of non-COVID infections have changed since the removal of measures during the COVID-19 pandemic. These changes may also impact febrile seizures, which are known to be triggered by infections.We aimed to reveal the frequency and seasonal distribution of febrile seizures during the COVID-19 pandemic and after the removal of social restrictions and measures. Methods: Patients who presented to the emergency department with a febrile seizure were grouped as having first or recurrent febrile seizure, and demographic data were reported. The patients were then grouped according to the period of the pandemic as follows; the first year of the pandemic (Group 1), the second year (Group 2), and the period after the removal of measures (Group 3). The groups were compared in terms of the number of patients, seizure age, seizure duration, seizure frequency, season of admission, seizure type, seizure status at the time of admission to the emergency department (stopped or ongoing), and electroencephalography (EEG) findings. Results: A total of 248 patients who presented with 272 febrile seizures were included. There were 34, 105, and 132 patients in Groups 1, 2, and 3, respectively. There were no significant differences among the three groups in terms of recurrent febrile seizures, continuation of seizures upon admission to the emergency department, duration of seizures, treatment requirement in the emergency department, or ratio of focal seizures (p>0,05). However, the number of febrile seizures increased in groups 2 and 3. There was seasonal variation in febrile seizures, with a decrease in autumn and an increase in winter. The majority of patients in all groups was under 3 years of age. Conclusions: In this study, we attributed the decrease in the number of febrile seizures in the first year of the pandemic period and its increase in the subsequent years to the effects of the pandemic on the course of infections. The seasonal shift observed in febrile seizures after the removal of precautions may also reflect changes in the period of infection. Understanding that pandemics cause epidemiological changes in infections and related comorbidities is important for the early prediction and management of infections and their comorbidities.